APPLYING DOMAIN PSYCHOMOTOR TEACHING METHODS IN VOCATIONAL COLLEGE - Madar, Ahmad Rizal; Sumarwati, Sri; Bakar, Nabilah Abu; Hamid, Hashima; Ibrahim, Azhani Che (International Journal of Psychosocial Rehabilitation, 2020)
The teaching method that used by teachers will be an impact on teaching and learning process. This study aims to discuss the practical teaching methods and practices dominant in the psychomotor domain of the practical teaching method adopted by the teacher in vocational college. The design of this study was oriented survey with quantitative approach and methods by observations of the teachers who teach at the workshop at a vocational college. Purposive sampling used to select in executing the method of observation. Number of samples selected in carrying out the method of observation is of four trainers who is chairman vocational workshops. The results showed that mean for the practical aspect of teaching methods of teaching design is 3.723, the implementation of teaching and evaluation of teaching is 3.542 and 3.504. For the implementation of teaching, teaching methods carried out showed the highest mean value for the recollection, the question, answer and presentation where the mean is about 4.06, 4.05 and 4.05. Then followed by the discussion and video screenings of 4.03 and 3.99. Overall, vocational college instructor more emphasis on teaching methods to the psychomotor domain observations, inventory, motion control, special movements, mechanisms and adjustment, but less emphasis on originality domain during the teaching and learning at the workshop. Psychomotor domain of the implementation by the instructors in teaching at workshops do not meet all seven standards psychomotor domains that has been set. The results of this study are expected to provide new ideas for teachers to apply all the skills in the psychomotor elements in the selection of appropriate teaching methods for teaching centered on practical workshops.